2015
DOI: 10.15408/ijies.v6i2.1228
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Indeks Harga Saham Syariah Internasional Dan Variabel Makro Ekonomi Terhadap Jakarta Islamic Index

Abstract: This research atempts to examine the impact of international Islamic stock market and macroeconomic variables towards Jakarta Islamic Index (JII). By using Vector Error Correction Model (VECM) as the method, this research utilizes time series monthly data from January 2007 to October 2012. The finding shows that JII is positively significantly affected by DJIEU, DJIMY and IPI, and it is negatively significantly affected by DJIJP, IMUS, M2 and SBIS.JII reaches its stability condition fastest when dealing with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 3 publications
2
14
0
4
Order By: Relevance
“…Sutrisno (2017) found that there are a positive relationship between volatility and trading frequency in the Indonesian stock exchange. Beik and Fatmawati (2014) found that macroeconomics variables such as M2 and Islamic Certificate of Bank Indonesia (SBIS) had an affect on Jakarta Islamic Index. Majid (2016) show that there is cointegration between Islamic stock prices and macroeconomics variables.…”
Section: Resultsmentioning
confidence: 99%
“…Sutrisno (2017) found that there are a positive relationship between volatility and trading frequency in the Indonesian stock exchange. Beik and Fatmawati (2014) found that macroeconomics variables such as M2 and Islamic Certificate of Bank Indonesia (SBIS) had an affect on Jakarta Islamic Index. Majid (2016) show that there is cointegration between Islamic stock prices and macroeconomics variables.…”
Section: Resultsmentioning
confidence: 99%
“…It means many investors are interested to invest in Islamic stocks. While the capitalization of Islamic stocks as indicated by the Jakarta Islamic Index (JII) had decreased in 2008 as a result of the subprime crisis in the United States [3]. The following table is the performance table of JII: TABLE I. Current stock prices tend to be influenced by psychological factors of the buyers or sellers of the shares themselves, causing a lot of speculation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Industrial Production Index is an economic indicator that measures the production of real output. IPI is often used as a representation of national income to replace the absence of monthly GDP data (Beik & Fatmawati, 2014). In Indonesia it is divided into large and medium industries and micro and small industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So that it will increase the amount of zakat. And IPI is often used as a representation of national income to replace the absence of monthly GDP data (Beik & Fatmawati, 2014). In Indonesia, the industrial sector is the largest contributor to Gross Domestic Product (GDP) each year.…”
Section: Based Onmentioning
confidence: 99%